2021
DOI: 10.1016/j.stemcr.2020.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Murine Myeloid Progenitors Attenuate Immune Dysfunction Induced by Hemorrhagic Shock

Abstract: Summary Hemorrhagic shock induces an aberrant immune response characterized by simultaneous induction of a proinflammatory state and impaired host defenses. The objective of this study was to evaluate the impact of conditionally immortalized neutrophil progenitors (NPs) on this aberrant immune response. We employed a mouse model of hemorrhagic shock, followed by the adoptive transfer of NPs and subsequent inoculation of Staphylococcus aureus to induce pneumonia. We observed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…We observed that HS induced an upregulation of these pro and anti-inflammatory cytokines. Similar results were recently reported in mice, showing an increase in circulating IL-6 and IL-10 cytokine levels 90 min and 24 h after HS [39]. These results are consistent with the clinical literature, including a study on a cohort of 89 adult trauma patients that revealed a leukocytosis, an elevated serum pro-and antiinflammatory cytokines, and evidence of innate cell activation, within minutes of trauma [26].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We observed that HS induced an upregulation of these pro and anti-inflammatory cytokines. Similar results were recently reported in mice, showing an increase in circulating IL-6 and IL-10 cytokine levels 90 min and 24 h after HS [39]. These results are consistent with the clinical literature, including a study on a cohort of 89 adult trauma patients that revealed a leukocytosis, an elevated serum pro-and antiinflammatory cytokines, and evidence of innate cell activation, within minutes of trauma [26].…”
Section: Discussionsupporting
confidence: 91%
“…They also observed a simultaneous induction of a hyperinflammatory state. They finally demonstrated that mice transplantation of neutrophil progenitors following HS decreases the proportion of host neutrophils with a suppressive phenotype and also attenuates their "priming" [39]. Therefore, MSCp therapy decreased both activation and inhibition markers on monocytes and granulocytes and the plasmatic expression of pro and anti-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Since the approach for conditionally immortalizing murine myeloid progenitors by exogenous expression of HoxB8 was initially described (Wang et al, 2006), others have shown that such progenitor cell lines can be transplanted into irradiated recipient mice and subsequently generate mature, terminally differentiated myeloid leukocytes in the in vivo environment (Gautam et al, 2013;Redecke et al, 2013;Orosz et al, 2021). Recently, we reported that a HoxB8-conditional progenitor cell line that we derived is able to produce substantial numbers of donor graft-derived neutrophils in mice that were not subjected to any conditioning of the hematopoietic niche (Cohen et al, 2021). To understand if the engraftment of HoxB8conditional progenitors in naïve, unconditioned mice was a unique feature of this particular progenitor cell line, we compared its engraftment to other lines of HoxB8-conditional myeloid progenitors using congenic CD45.1 recipient mice.…”
Section: Engraftment Of Hoxb8-conditional Progenitorsmentioning
confidence: 92%
“…HoxB8 conditionally-immortalized progenitors. As described previously (Cohen et al, 2021), a lentivirus-based construct with a tamoxifen-inducible Hoxb8 oncogene (Salmanidis et al, 2013) (a gift from Paul Ekert, Murdoch Children's Research Institute) with either a puromycin or hygromycin resistance cassette was used to stably express HoxB8 in bone marrow hematopoietic stem and progenitor cells (HSPCs) isolated from C57BL/6J mice. HSPCs were cultured with recombinant murine stem cell factor (SCF) and interleukin-3 (IL-3) for two days, exactly as described (Wang et al, 2006), and then subjected to spin-infection (2000 RPM, 60 min, 30°C) with lentivirus in a 24-well plate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation